2012
DOI: 10.1016/j.jeap.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse repertoire of L1 Mandarin undergraduates writing in English: A cross-contextual, cross-disciplinary study

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription. AbstractThis article presents a qualitative, comparative study of metadiscourse in the academic writing of two groups of undergraduate students working in two different disciplines. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 28 publications
(27 reference statements)
13
69
1
4
Order By: Relevance
“…Such a finding is not surprising as it is synonymous to most results obtained in past studies (see e.g. Hyland, 2004;Letsoela, 2013;Li & Wharton, 2012). It could be that transitions are fundamental linguistic elements that have been taught to students in grammar and writing classes.…”
Section: Frequency Of Use Of the Different Categories Of Interactive supporting
confidence: 77%
See 1 more Smart Citation
“…Such a finding is not surprising as it is synonymous to most results obtained in past studies (see e.g. Hyland, 2004;Letsoela, 2013;Li & Wharton, 2012). It could be that transitions are fundamental linguistic elements that have been taught to students in grammar and writing classes.…”
Section: Frequency Of Use Of the Different Categories Of Interactive supporting
confidence: 77%
“…It was also found that the Finnish students had a higher density of metadiscourse per line and they used more hedges than the American students. In Li and Wharton's (2012) cross cultural and cross disciplinary study on the metadiscourse repertoire of L1Mandarin undergraduates' writing in English in China and in the UK, it was found that there were disciplinary variations in the use of metadiscourse. However, they argued that context was a more influential factor as they found interesting differences in metadiscourse use between contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has also suggested that local institutional culture may influence writers' deployment of interpersonal resources; for example Li & Wharton (2012) found that context, rather than discipline, was an influencing factor in writers' metadiscourse choices. Dahl (2004) argues that patterning of textual metadiscourse is influenced both by disciplinary culture and by L1 writing culture, but also shows that disciplinary culture can transcend national culture in research writing in disciplines such as Medicine with a stable and homogeneous knowledge base and structure for research reporting.…”
Section: Resultsmentioning
confidence: 99%
“…These findings also show English writers' preference for a progressive style over the retrogressive style previously used, one that employs more additive devices than comparative and consequence devices. Arab writers also employed the same progressive style over the retrogressive style with approximately the same ratio (2:1) as a result of using the same writing genre to meet the demands of their departmental, institutional, field micro-communities (Lee & Casal, 2014;Roberts & Cimasko, 2008;Li & Wharton, 2012). Differences in the frequency use of these transition devices in these three sub-categories are to be attributed to divergent degrees of experience in composing research genres between the writers in the two corpora and between novice and expert L2 writers in the ArbWDCs group (Hyland, 2008).…”
Section: B Within Each Interactive Subcategory What Were the Differmentioning
confidence: 99%
“…Students in general strive to demonstrating their competence in conducting original research, presenting pertinent knowledge of research field literature and producing high-quality writing in the form of theses or dissertations to meet the demands of their departmental, institutional, and later, field micro-communities (Lee & Casal, 2014;Roberts & Cimasko, 2008;Li & Wharton, 2012). Theses and dissertations are distinctive genres due to their differing purpose, rhetorical structures, and immediate reader expectations (Thompson, 2013).…”
Section: Introductionmentioning
confidence: 99%